Pengaruh Religiusitas dan Pengetahuan Halal Terhadap Minat Berkunjung pada Objek Wisata di Malang Raya - Arta, Aris Danu; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2021)
The current globalization has changed the paradigm of society towards tourism to make it part of the lifestyle. Increasingly massive and uncontrolled developments must still involve the role of religion so as not to break the rules. Muslim tourists as consumers are required to be more critical of the guarantee of tourist activities in accordance with sharia principles. The purpose of this research is to know the influence of religiosity and halal knowledge as a reflection of the critical attitude of tourists to the interest in visiting tourist attractions in Malang Raya. The research was conducted with quantitative approach through multiple linear regression analysis. The research population is the Muslim community of Surabaya city of 85.5% of the total population in 2020. Then, for the research sample of 100 respondents according to the calculation with slovin formula. Data collection utilizes questionnaire instruments and is processed with SPSS version 23 application. The results showed that religiosity had an insignificant effect on visiting interests. Meanwhile, halal knowledge has a significant effect on the interest in visiting. Then, simultaneously, the variables of religiosity and halal knowledge affect the interest of visiting.